2019
DOI: 10.1371/journal.pone.0216717
|View full text |Cite
|
Sign up to set email alerts
|

Agromorphologic, genetic and methylation profiling of Dioscorea and Musa species multiplied under three micropropagation systems

Abstract: Plant in vitro vegetative propagation using classical semi-solid culture medium is limited due to the low degree of automation, suboptimal nutrient availability and induced physiological stress which often reduce its efficiency. Temporary Immersion System (TIS) emerged as an innovative approach to optimize and eliminate the drawbacks associated with the conventional system of micropropagation. In this study, both Dioscorea and Musa spp. were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The occurrence of genetic variation in micro-propagated banana plants mainly due to the use of a higher concentration of growth regulators and an increased number of subcultures as a response to the stress imposed on the plant during the culture period. It has been demonstrated in the form of DNA methylations, chromosome rearrangements and point mutations 16 , 27 , 58 , 59 . To access the genetic uniformity, DNA-based molecular markers of ISSR are widely used 60 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of genetic variation in micro-propagated banana plants mainly due to the use of a higher concentration of growth regulators and an increased number of subcultures as a response to the stress imposed on the plant during the culture period. It has been demonstrated in the form of DNA methylations, chromosome rearrangements and point mutations 16 , 27 , 58 , 59 . To access the genetic uniformity, DNA-based molecular markers of ISSR are widely used 60 .…”
Section: Discussionmentioning
confidence: 99%
“…The high production cost prevents small- or medium-scale laboratories with limited resources from accessing the potential benefits of plant tissue culture technology 15 . Recent studies have been proposed to utilize automated temporary immersion systems (TIS), which is less expensive and provides an optimal environment for in vitro plant cell, tissue and organ cultures with good productivity 16 18 . Over the years, several temporary immersion systems have been developed and successfully applied for in vitro propagation of banana 19 25 .…”
Section: Introductionmentioning
confidence: 99%
“…With the development of knowledge on tissue cultures, it has been proven that the conditions used in vitro may lead to changes in regenerated plants. Apart from morphological [ 60 ] also genetic [ 61 ] and epigenetic [ 39 , 42 , 62 ] alterations between regenerants and donor plants are observed and quantified by the metAFLP approach [ 42 ]. The metAFLP approach showed that it is sufficiently informative for analysis of even closely related species as well as tissue culture-derived regenerants [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies on in vitro culture related to conservation procedures (slow growth and cryopreservation) do not report how many DNA samples from each experimental condition were used to perform the MSAP analysis. In some cases, a single sample was used per experimental condition, it being sometimes a pool of several samples [ 111 , 121 , 122 , 123 ]. Or the fragments obtained from the different analyzed samples were counted together without considering the variability between the samples within each experimental condition.…”
Section: Statistical Methods For Msap Analysis In Plant Conservatimentioning
confidence: 99%
“…When a statistical analysis was carried out, most of the published works used the multivariate techniques proposed in the studies of population epigenetics [ 80 , 98 , 123 ]. These methods are suitable in the context of population epigenetics, where a large number of individuals within the population are measured and the interest is to quantify diversity based on differences of DNA methylation markers between populations.…”
Section: Statistical Methods For Msap Analysis In Plant Conservatimentioning
confidence: 99%